부식산 액상비료 시비에 의한 크리핑 벤트그래스 지하부 생육증가와 품질향상 - 이긍주(Geung-Joo Lee); 조성현(Sung-Hyun Cho); 이태순(Tae-Soon Lee); 김영선(Young-Sun Kim) (Weed & turfgrass science, 2018)
This study was conducted to evaluate the effect of liquid fertilizer containing humate (LFH) on changes of turfgrass quality and growth by investigating visual quality, chlorophyll content, dry weight of clipping, and nutrient content in leaves tissue. Treatments were designed as follows; control fertilizer (CF), HF-1 ($CF+1.0mL\;m^{-2}\;LFH$), HF-2 ($CF+2.0mL\;m^{-2}\;LFH$), and HF-3 ($CF+4.0mL\;m^{-2}\;LFH$). As compared with CF, soil chemical properties of LFH treatments were not significantly. Visual quality and root dry weight of LFH treatments were higher than that of CF. Chlorophyll content, clipping yield and nitrogen uptake of HF-2 and HF-3 were increased 11.2-11.8%, 15.3-30.0%, 22-42% by application of LFH. The LFH level was positively correlated with visual quality, chlorophyll content, clipping yield or nutrient uptake amount. These results indicated that the application of LFH improved the growth and quality of creeping bentgrass by increasing nutrient uptake and by prompting root growth. 본 연구는 부식산 함유 액비(LFH)의 시비에 따른 크리핑 벤트그래스의 생육과 품질의 변화를 확인하기 위해 잔디의 가시적 품질, 엽록소 함량, 예지물량, T/R ratio, 양분 함량 및 흡수량을 조사하였다. 처리구는 대조구(CF), LFH 1,000배 처리구(HF-1), LFH 500배 처리구(HF-2) 및 LFH 250배 처리구(HF-3)로 구분되었다. LFH 처리 전후에 토양화학성은 차이를 나타내지 않았다. LFH처리구와 대조구를 비교하였을 때, 가시적 품질과 뿌리 생육량은 LFH처리구에서 증가하였고, 엽록소 함량, 잔디 예지물, 질소 흡수량은 HF-2처리구와 HF-3처리구에서 각각 11.2-11.8%, 15.3-30.8%, 22-42%씩 증가하였다. LFH처리량에 따라 가시적 품질, 엽록소 함량, 잔디 예지물 및 양분 흡수량은 정의 상관성을 나타내었다. 이 결과들을 종합해 볼 때, 크리핑 벤트그래스에서 부식산 함유 액비의 시비는 잔디의 잎 조직 중 잔디지하부의 생육이 증가하여 양분 흡수를 개선함으로써 잔디품질과 생육이 증가하는 것을 확인 할 수 있었다.